Everyday Nationhood : Theorising Culture, Identity and Belonging after Banal Nationalism - Skey, Michael; Antonsich, Marco (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This edited collection explores the continuing appeal of nationalism around the world. The authors' ground-breaking research demonstrates the ways in which national priorities and sensibilities frame an extraordinary array of activities, from classroom discussions and social media posts to global policy-making, as well as identifying the value that can come from feeling part of a national community, especially during times of economic uncertainty and social change. They also note how attachments to nation can often generate powerful emotions, happiness and pride as well as anger and frustration, which can be used to mobilize substantial numbers of people into action. Featuring contributions from leading social scientists across a range of disciplines, including sociology, geography, political science, social psychology, media and cultural studies, the book presents a number of case studies covering a range of countries including Russia, USA, New Zealand, Serbia, Japan and Greece. Everyday Nationhood will appeal to students and scholars of nationalism, globalization and identity across the social sciences as well as those with an interest in understanding the role of nationalism in shaping some of the most pressing political crises- migration, economic protectionism, populism - of the contemporary era. .
Keywords: Social sciences.; Religion and culture.; Ethnicity.; elektronické knihy; electronic books